Jaltomata veracruzana (Solaneae, Solanoideae, Solanaceae), a new species from the mountain cloud forests of Veracruz, Mexico - Martínez-Flores, Ma. Mercedes; Burgos-Hernández, Mireya; Martínez-Domínguez, Lilí; Nicolalde-Morejón, Fernando (Phytotaxa, 2025)
A new species from the state of Veracruz, Mexico, previously identified as Jaltomata bohsiana, is described as Jaltomata veracruzana. This species occurs in the mountain cloud forest of the Sierra de Chiconquiaco. It can be distinguished from its congeners by the combination of a black to blackish calyx when in flower, pubescence sparse, corolla with light-purple veins, green pedicels, and ovate-deltoid leaves with sinuate to sinuate-toothed margins, acute apex, and attenuated-truncated base. A preliminary conservation assessment is provided for this new species based on IUCN Red List guidelines. We provide a detailed comparison of this new species with all Jaltomata species distributed in Mexico, including a full description, illustrations, taxonomic notes, comparative table, and an identification key for the genus in Mexico.